Ethics and cyber warfare the quest for responsible security in the age of digital warfare - Lucas, George R. (Oxford University Press, 2017)
Given the prevalence of cyber warfare, developing a practical moral code for this new form of conflict is more important than ever. In Ethics and Cyber Warfare, internationally-respected ethicist George Lucas delves into the confounding realm of cyber conflict.